The Effect of Product Quality, Brand Image, and Price Perception on Wardah Product Purchase Decisions - Febsri Susanti Febsri (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Study This aim For analyze influence quality product, image brand, and perception price to decision purchase product Wardah cosmetics on consumers in Padang City. Research use approach quantitative with method survey. Population study is all over consumers who have ever buy and use Wardah products in Padang City. Sample collection technique sample using purposive sampling with amount respondents as many as 200 people. Data collection was carried out through distribution questionnaire use Likert scale 1–5. Data analysis using multiple linear regression with SPSS software assistance. Research results show that quality product, image brand, and perception price influential positive and significant to decision purchase Wardah products. In general simultaneous third variables independent capable explain variation decision purchase consumers . Findings This indicates that improvement quality product, strengthening image brand, and determination appropriate price​ can increase decision purchase consumer to Wardah products in Padang City. Findings This in line with various study previously shown​ that quality product, image brand and price is determinant main decision purchase Wardah products.